Empty Fruit Bunch (EFB) as planting medium for mushroom / Muhamad Hafizulhelmi Harun - Harun, Muhamad Hafizulhelmi (Faculty of Plantation and Agrotechnology, 2016)
One of Malaysia major crop is the oil palm. Oil palm industry produce many types of waste product such as empty fruit bunch and the press palm fiber which can cause pollution to the environment. This waste contain a lot of lignocellulosic materials that suitable for mushroom growth. Usually, mushroom are grow using saw dust by the industry. Due to the high demand for mushroom, the resource for saw dust cannot meet with the demand. So, this paper is done to identify uses of empty fruit bunch as the mushroom planting medium in term of solve the problem of oil palm waste product that can cause pollution and lack of resources for growing mushroom. By utilizing the waste product, income can be generated by producing high protein food product. So, it can contribute to improve sources of food product to the country.